The Change of the Kinetics Model in the Calculations of Fast-Neutron Reactors; AIP Conference Proceedings; Vol. 2212 : Thermophysical Basis of Energy Technologies (TBET 2019) - Savitsky D. E. Denis (2020, 2020)
Title screen